The right nation conservative power in America - Micklethwait, John; Wooldridge, Adrian (Penguin Press, 2004)
Two renowned British America-watchers anatomize the conservative movement and explain how it has stamped its program so deeply into American life. This book is for anyone who wants to understand one of the most important forces shaping American life. How did America's government become so much more conservative in just a generation? Welfare is gone; the death penalty is deeply rooted; abortion is under siege; regulations are being rolled back; the pillars of New Deal liberalism are turning to sand. Conservative positions have not prevailed everywhere, of course, but this book shows us why they've been so successfully advanced over such a broad front: because the battle has been waged by well-organized, shrewd, and committed troops who to some extent have been lucky in their enemies. The authors come neither to bury the American conservative movement nor to praise it blindly but to understand it, in all its dimensions.--From publisher description.
Keywords: Geschichte 1900-2000; Geschichte; Conservatisme - États-Unis - Histoire - 20e siècle; Conservatisme; Droite (Science politique); Konservatism - Förenta staterna - historia - 1900-talet; Politik; Conservatism -- United States -- History -- 20th century; Right and left (Political science) -- History -- 20th century; Die Rechte; Konservativismus; Förenta staterna - politik och förvaltning - historia - 1900-talet; États-Unis - Politique et gouvernement - 20e siècle; USA; United States -- Politics and government -- 20th century